WATER – ENERGY NEXUS: ARSITEKTUR SISTEM PENGELOLAAN AIR DAN ENERGI ALTERNATIF DI KAMPUNG TELUK GONG – JAKARTA UTARA - Salsabila, Annisa Diva; Sutanto, Agustinus (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2025)
Kampung Teluk Gong in North Jakarta is currently facing a critical shortage of clean water due to waste pollution and inadequate sanitation infrastructure. This paper presents a regenerative architectural solution through the Water–Energy Nexus approach, which integrates rainwater and floodwater treatment systems into clean water sources while utilizing them as an alternative energy supply. The study is focused on a micro-site scale using a community-based design approach, without exploring broader aspects such as policy, macroeconomic considerations, or city-wide utility systems. The scope is limited to: (1) social and site analysis in Kampung Teluk Gong; (2) the application of simple technologies such as water filtration and structure-based micro-hydro systems; and (3) spatial programming that responds to local climate and community habits. The “Oasis of Peace” project serves as a conceptual reference for sustainable water systems, but only as a programmatic inspiration. The design centers on a multifunctional building with three primary zones: sustainable housing, clean water distribution, and social-educational spaces. The findings indicate that a modular stepwell design can contextually address basic water and energy needs. This paper does not include technical simulations or numerical efficiency calculations, thus offering opportunities for future research on structural and technological aspects. Keywords: architecture; clean water; regenerative; residential; village Abstrak Kampung Teluk Gong di Jakarta Utara saat ini menghadapi masalah ketersediaan air bersih akibat pencemaran limbah dan kurangnya infrastruktur sanitasi. Tulisan ini menguraikan solusi arsitektur regeneratif dengan pendekatan Water–Energy Nexus, yang mencakup penggabungan sistem pengolahan air hujan dan banjir menjadi air bersih serta pemanfaatannya sebagai sumber energi alternatif. Penelitian ini berfokus pada skala tapak mikro dengan pendekatan desain yang berbasis komunitas, tanpa mengkaji aspek kebijakan, ekonomi makro, atau sistem utilitas kota secara umum. Pembahasan terbatas pada: (1) analisis sosial dan lokasi di Kampung Teluk Gong; (2) penggunaan teknologi sederhana seperti filtrasi air dan mikrohidro berbasis struktur; serta (3) pengembangan program ruang yang responsif terhadap iklim dan kebiasaan masyarakat. Studi kasus "Oasis of Peace" dijadikan acuan untuk konsep sistem air berkelanjutan, tetapi hanya sebagai sumber inspirasi untuk program. Desain berfokus pada gedung serbaguna dengan tiga area utama: hunian berkelanjutan, penyediaan air bersih, dan tempat sosial untuk pendidikan. Temuan menunjukkan bahwa rancangan stepwell dapat memenuhi kebutuhan mendasar akan air dan energi masyarakat secara kontekstual. Jurnal ini tidak menyertakan simulasi teknis sistem air atau perhitungan efisiensi energi secara numerik, sehingga memberikan peluang penelitian lebih lanjut pada aspek struktural dan teknologi di masa yang akan datang.